Olfactory, Auditory, and Vestibular Performance: Multisensory Impairment Is Significantly Associated With Incident Cognitive Impairment - Lucas, Jacob C.; Arambula, Zack; Arambula, Alexandra M.; Yu, Katherine; Farrokhian, Nathan; D'Silva, Linda; Staecker, Hinrich; Villwock, Jennifer A. (Frontiers in Neurology, 2022)
Background Dysfunction in the olfactory, auditory, and vestibular systems are commonly seen in aging and are associated with dementia. The impact of sensory loss(es) on cognition is not well understood. Our aim was to assess the relationships between performance on objective multisensory testing and quantify the impact of dysfunction on cognition. Methods Patients presenting with subjective hearing loss presenting to a tertiary care otologic/audiologic clinic were identified and underwent multisensory testing using the Affordable, Rapid Olfactory Measurement Array (AROMA), pure tone audiometric evaluations, and the Timed “Up and Go” test. Cognitive impairment (CI) was assessed via the Montreal Cognitive Assessment (MoCA) was also administered. Key Results 180 patients were enrolled. Thirty one percentage (n = 57) screened positive for cognitive impairment. When evaluating single sensory impairments, we found that olfactory dysfunction, gait impairment, and sensorineural hearing loss were all statistically significantly (p < 0.05) associated with a higher risk of cognitive impairment (ORs 3.89, 3.49, and 2.78, respectively) for CI. Multisensory impairment was significantly associated with cognitive impairment. Subjects with dysfunction in all domains were at the highest risk for cognitive impairment (OR 15.7, p < 0.001) vs. those with impairment in 2 domains (OR 5.32, p < 0.001). Conclusion Dysfunction of the olfactory, auditory, and vestibular systems is associated with a significantly increased risk of CI. The dramatically increased risk of CI with multisensory dysfunction in all three systems indicated that MSD may synergistically contribute to CI.